Antena Â½ Folded Dipole Vertikal untuk Komunikasi Jarak Sedang - Basuki, Hari Satriyo (Pusat Penelitian Informatika - LIPI, 2007)
There are many antenna type used in high frequency band for medium range communication such as Dipole, Yogi, Folded Dipole, Zeppelin, Log Periodic and others. But when the space to erect the antenna is limited, it will be used a special antenna that has an optimum performance and good for the reception and transmitter function. In this limited space problem and the need to cover a wide area some antenna can be used such as Vertical, Inverted Vee, Lazy Loop, Quad and others. Many problems will be occurred to erect the limited space antennas such as the impedance, take off angle and the pattern. In this paper will be discussed a special antenna that basically vertical dipole, its impedance measurement, feeding point, and many things.Keywords: vertical antenna,1/2 folded dipole, short distance communications